Peningkatan Keterampilan Membaca Pemahaman Melalui Model Cooperative Integrated Reading And Compotition Siswa Kelas 4 SD - Ningrum, Yunita; Kristin, Firosalia (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2019)
The learning process requires several skills that need to be mastered by students, one of which is reading comprehension skills. The learning process in Kutowinangun 04 of elementary school has problems with the low reading comprehension skills. The low reading skills resulted in the results of reading comprehension skills not being optimal. This study aims to improve reading comprehension skills through the application of the Cooperative Integrated Reading and Compotition model. Data collection techniques used were observation sheets to collect data on reading comprehension skills and student activities supported by documentation to prove activities during the learning process. The data analysis technique uses quantitative data and qualitative data analysis. The results of the study of reading comprehension skills using the Cooperative Integrated Reading and Compotition (CIRC) model showed an increase in the percentage of the average reading comprehension skill based on the category of 11.78%, that is from 60.34% (categories need guidance) in pre-action which increased to 72 , 12% (good category) in the first cycle, then increased again by 18.02% from 72.12% (good category) in the first cycle increased to 90.14% (very good category) on cycles II. It can be concluded that the application of the Cooperative Integrated Reading and Compotition (CIRC) method can improve reading comprehension skills.